Coagulation of luminescent colloid nGdVO₄:Eu solutions with inorganic electrolytes - Klochkov, V.K. (Functional Materials, 2009)
Aqueous colloid solutions of europium-doped gadolinium orthovanadates have been prepared. The nanoparticles of about 20 nm diameter show a bright luminescence. The aqueous nGdVO₄:Eu solutions are transparent in the visible region and maintain the unchanged properties for more than two months. The presence of inorganic salts causes a reduction of the solution aggregative stability. The aggregation threshold values are in a close correspondence with the Schultze-Hardy rule and the 6th power Deryagin-Landau law for "negative" lyophobic sols.